Epidemiology of Fracture Dislocations 1 Year Trend at a Peripheral Hospital in India - Sarla, Gurmeet Singh (Eastern Journal of Medical Sciences, 2018)
Introduction: The epidemiology of fracture dislocations is poorly understood. In this study we aimed to evaluate the prevalence and distribution of various fracture dislocations in the department of General Surgery in a peripheral hospital in Nasik. Material and methods: Fracture dislocation cases who underwent closed reduction by a general surgeon where no orthopaedician was available at a peripheral hospital in Devlali, Nasik from January 2017 to December 2017, were recorded. The demographic details of the patients who reported to this hospital were extracted and the type and site of fracture dislocations were classified according to their age and gender groups. Results: Out of the 47 patients, 30 patients (63.82%) were male and 17 patients (36.17%) were female. The highest incidence, 13 patients (27.65%) occurred in the age group of 20-30 years. In males, the highest incidence i.e. 10 patients (33.33%) occurred in the age group of 20-30 years. In females, the highest incidence i.e. 6 patients (12.76%) occurred in the age group of 60-70 years. A total of 11 cases (23.40%), the highest incidence occurred in the month of February. 31 cases of fracture dislocation were right sided (65.95%) and 16 patients had fracture dislocation on the left side (34.04%). 14 cases (29.78%) were of fracture lower end of radius which was the most common fracture encountered. Conclusion: Fracture lower end of radius was the most common fracture encountered; males sustained higher incidence of fracture dislocations and the age group of 20-30 years was most commonly involved. In females, the highest incidence occurred in the age group of 60-70 years. Left upper limb was more commonly involved in fracture dislocations of our series. The highest incidence occurred in the month of February.